2020
DOI: 10.1021/acs.langmuir.0c02391
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Linkages of Molecules and Proteins to Si–H Surfaces Formed by Disulfide Reduction

Abstract: Thiols and disulfides contacts have been, for decades, key for connecting organic molecules to surfaces and nanoclusters as they form self-assembled monolayers (SAMs) on metals such as gold (Au) under mild conditions. In contrast, they have not been similarly deployed on Si owing to the harsh conditions required for monolayers formation. Here, we show that SAMs can be simply formed by dipping Si−H surfaces into dilute solutions of organic molecules or proteins comprising disulfide bonds. We demonstrate that S−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 92 publications
(167 reference statements)
1
24
0
Order By: Relevance
“…XRR analysis details and fitting parameters are discussed in supporting information (Table S1). AFM imaging for the functionalized Si-H surfaces shows smooth edges and individual flat terraces of roughness~0.2 nm (Figure 2e,f), consistent with results from typical alkyne/alkene monolayers formed on Si-H [16,34]. Further, AFM images for non-functionalized Si-H surfaces ( Figure S3) showed minimal change after functionalization demonstrating that the monolayers are formed smoothly without causing any dramatic changes to the crystalline Si surface.…”
Section: Electrochemical Measurementssupporting
confidence: 78%
See 1 more Smart Citation
“…XRR analysis details and fitting parameters are discussed in supporting information (Table S1). AFM imaging for the functionalized Si-H surfaces shows smooth edges and individual flat terraces of roughness~0.2 nm (Figure 2e,f), consistent with results from typical alkyne/alkene monolayers formed on Si-H [16,34]. Further, AFM images for non-functionalized Si-H surfaces ( Figure S3) showed minimal change after functionalization demonstrating that the monolayers are formed smoothly without causing any dramatic changes to the crystalline Si surface.…”
Section: Electrochemical Measurementssupporting
confidence: 78%
“…Recently, we have demonstrated that spontaneous nanoscale corrosion of Si-H surfaces leads to disulfide bond breaking and enables the formation of high-quality SAMs of thiols and disulfides on Si [16,34]. In this study, we turn our attention to OH contact groups as they are commonly available functionalities that could broaden the source of the organic molecules that can form monolayers on Si.…”
Section: Introductionmentioning
confidence: 99%
“…A key feature of the synthesis conditions recently developed 1,2 is that they require no heating, pressure, irradiation, or external catalysis. This differs from the wide variety of approaches previously used for grafting molecules onto silicon 3 using, e.g., [4][5][6] Lewis acids, 7 Grignard reagents, 8,9 electrografting, 10 and microwave 11 or UV-Visible irradiation, [12][13][14][15][16][17][18] involving perhaps ultra-high vacuum technologies, 19,20 hightemperature solution chemistry, 21,22 or high-temperature highpressure processes in supercritical CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, synthetic techniques compatible with technologies used in silicon fabrication plants were developed that can assemble molecules with either thiol 1 or disulfide 2 terminating groups between two silicon-electrode contacts. This can, in principle, pave the way for the inclusion of single-molecules, or else nanoscopic self-assembled monolayers (SAMs), to be imbedded into silicon diodes and transistors.…”
Section: Introductionmentioning
confidence: 99%
“…Grafting of sulfhydryls on to SiH surfaces have been investigated with some success by UV illumination, [ 77 ] heat, [ 78 ] or electrochemical grafting. [ 79 ] The later recently published electrochemical grafting protocol interestingly showed monolayer formation under ambient condition that may even proceed spontaneously without applied voltage or catalyst. They suggested that the formation of the monolayer, formed within an hour is guided by water generating local nanoscale oxidation of the Si surface.…”
Section: Grafting Organic Molecules To H Passivated Siliconmentioning
confidence: 99%